2008
DOI: 10.1117/12.780061
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure and optical properties of biological polarizers in crustaceans and cephalopods

Abstract: The lighting of the underwater environment is constantly changing due to attenuation by water, scattering by suspended particles, as well as the refraction and reflection caused by the surface waves. These factors pose a great challenge for marine animals which communicate through visual signals, especially those based on color. To escape this problem, certain cephalopod mollusks and stomatopod crustaceans utilize the polarization properties of light. While the mechanisms behind the polarization vision of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the marine world of these highly successful invertebrate groups is the arms race or selection for polarisation secrecy still underway? Stomatopods possess circular polarisation vision and circular polarising signals, and these are not visible to cephalopods as far as we know (Figs 2D, 6 and 7G;Chiou et al, 2005Chiou et al, , 2007Chiou et al, , 2008a. Does this indicate a step ahead in the communication arms race?…”
Section: Circular Polarisation and The Case For Covert Communicationmentioning
confidence: 85%
See 2 more Smart Citations
“…In the marine world of these highly successful invertebrate groups is the arms race or selection for polarisation secrecy still underway? Stomatopods possess circular polarisation vision and circular polarising signals, and these are not visible to cephalopods as far as we know (Figs 2D, 6 and 7G;Chiou et al, 2005Chiou et al, , 2007Chiou et al, , 2008a. Does this indicate a step ahead in the communication arms race?…”
Section: Circular Polarisation and The Case For Covert Communicationmentioning
confidence: 85%
“…The result is a strong horizontal signal against a non-polarising background, ( Fig. 4; Chiou et al, 2005Chiou et al, , 2008aHow et al, 2014b;Cronin, 2018). Marshall (2010, 2011) showed that cuttlefish and squid orient the microvilli in adjacent photoreceptors mainly H and V relative to the outside world (Fig.…”
Section: Signal Orientation Confounding Parameters and Polarisation mentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization vision is widespread in nature ( Roberts et al, 2011 ), mainly among the invertebrates, where it contributes to a variety of behavioural tasks including navigation ( Wehner, 1976 ), habitat localization ( Schwind, 1991 ) and communication ( Chiou et al, 2008 ). In terrestrial environments, this sensory capacity is best understood in the dorsal rim area of the eye, which is directed towards the sky to enable the detection of the pattern of celestial polarization ( Wehner, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also crayfish visual motion detection [ 9 ], the predation of transparent zooplankton by marine life [ 10 ], and fiddler crab detection of objects in mudflats and other environments [ 11 ]. Among those polarization-sensitive creatures, cephalopods and crustaceans are in the majority [ 12 ]. Their representatives are octopuses and mantis shrimp, respectively, and there are corresponding bionic studies of these creatures, such as the polarized vision chip made by simulating the octopus retina [ 13 ] and the biomedical polarization imaging sensor inspired by the compound eyes of the mantis shrimp [ 14 ].…”
Section: Introductionmentioning
confidence: 99%